Analysis of Information Technology Services Using the ITIL V.3 Framework - Mahardika, Wildan Kristian; Emanuel, Andi Wahju Rahardjo (Jurnal Sisfokom (Sistem Informasi dan Komputer), 2023)
Information technology services have been widely used in various agencies. This is done because information technology services help many business processes in an agency. Government agencies, companies, and education are examples of agencies that utilize information technology services to support their business processes. One educational institution that uses IT services to support its business processes is the UKDW library. The UKDW Library utilizes IT services for borrowing, returning, searching for books and journals, checking for plagiarism, and more. To further improve the quality of IT services, evaluating and developing them is necessary to better respond to business needs. In this study, researchers measured the maturity level of an IT service in the UKDW library. Researchers use the ITIL V3 framework in measuring maturity levels. This research focuses on the service operation domain and its five sub-domains (problem management, event management, incident management, access management, and request fulfillment). The final results of the study show that IT services in the UKDW library are at the managed level, which means that information technology services in the UKDW library have been planned and carried out routinely. There are standards for documentation, and process performance measurement has been implemented.